Analisis Budaya Organisasi di PT FIFGROUP Dalam Rangka Meningkatkan Kinerja Perusahaan - Nugroho, Ferdy Setya (Business and Enterpreneurship Journal (BEJ), 2024)
Organizational culture is a very important identity for every organization or company. This is a key factor in improving employee performance in a company. The purpose of this writing is to determine the important role of Organizational Culture at PT FIFGROUP in order to Improve Company Performance. This research uses qualitative methods which are used to find out or describe the reality of the events being studied, making it easier to obtain objective data. The research results show that the organizational culture at FIFGROUP has a very important influence on improving the company's performance and the company's growth in a better direction. Keywords : Organizational, Culture, Company, Performance